Data-driven analysis and integrated modeling of climate change impacts on coastal groundwater and sanitary sewer infrastructure - Sangsefidi, Yousef; Barnes, Austin; Merrifield, Mark; Davani, Hassan (Sustainable cities and society, 2023)
•Sea-level rise (SLR) may impact inland sewer infrastructure kilometers away from the coastline.•More than 1/3 of the sanitary sewer length in Imperial Beach is subject to groundwater intrusion.•Defect flows may place $0.5−$2.7 M additional cost on the sanitary sewer system every year.•The elevated hydraulic loading can increase the potential of sanitary sewer overflows. The variation of the coastal groundwater table and the vulnerability of sanitary sewer infrastructure under a changing climate is considered for Imperial Beach (CA, USA) by incorporating the compound impacts of Sea-Level Rise (SLR), groundwater shoaling, and precipitation intensification. For 2 m of SLR, marine inundation is expected to impact only 2% of the urbanized area; however, SLR-driven groundwater shoaling is projected to impact 36% of the subterranean sewer system. Due to GroundWater Infiltration (GWI) and Rainfall-Derived Inflow and Infiltration (RDII), the sanitary sewage flow increases by 21% and 49% during dry- (i.e., consecutive days without precipitation) and wet-weather conditions (i.e., 24-hour rainfall with a 25-year return period), respectively. At SLR = 2 m, defect flows (GWI + RDII) can be elevated by 84% and 120% in dry- and wet-weather conditions, respectively. Such elevated hydraulic loads may place $0.5−$2.7 M additional cost on the collection system and treatment facilities every year. Moreover, pressurized junctions due to the above-mentioned hydraulic loading are likely to expose the community and the environment to raw sewage pollution. By involving structural, hydrological, and hydraulic criteria, a holistic approach is presented and implemented for prioritizing sewer system rehabilitation.